Assessment of the characteristics of the medical care teachers who train the Maternal and Child Health Nursing specialists - Norma Mur Villar; Miriam Iglesias León; Manuel Eduardo Cortés Cortés; María José Aguilar Cordero (Medisur)
Backgrounds: The features of the Mother and Child Health Nursing specialist’s teaching care training are paramount to form appropriate teaching behaviors. Aim: To determine the features of the medical care teacher who trains the Mother and Child Health Nursing specialist. Methods: An exploratory research was carried out during the years 2008-2009 in the “Gustavo Aldereguía Lima” General University Hospital of Cienfuegos, Decision Theory was applied to select the criteria taken into account in the Multicriterial model, by means of a variation of the Delphi Method. The universe was made up by the coordinators and methodologists who run the Mother and Child Health Nursing specialty on a national level, and a non-probabilistic sampling was conducted to obtain the Sample (Experts Sampling). Results: 23 criteria exceeding the PC4 cutoff point corresponding to the “much” category are needed, which links the professional model to the social demands to know, relate and apply the contents of nursing using the material resources that connect the concrete to the abstract to promote the continuity of medical care and the use of the potential of assistance in the training the specialists in which the professional’s behavior was demonstrated. Conclusions: By means of the stated criteria, it is evidenced that medical care is the basis for the kind of teaching training our professional needs to organize the teaching process, starting from medical care issues. That training allows them to accomplish their social task as health trainers.